2015
DOI: 10.1093/ajae/aav039
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Food Deserts on the Body Mass Index of Elementary Schoolchildren

Abstract: Families in low‐income neighborhoods sometimes lack access to supermarkets that provide a broad range of healthy foods. We investigate whether these so called “food deserts” play a role in childhood obesity using a statewide panel data set of Arkansas elementary schoolchildren. We use fixed‐effects panel data regression models to estimate the average food desert effect. We next compare children who left (entered) food deserts to children who were always (never) in food deserts and homogenize samples for those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 48 publications
0
29
0
Order By: Relevance
“…One class investigates the relationship between the local food environment and health outcomes. While this research offers mixed results, many studies do find a link between low food access and obesity, diabetes, and other health-related outcomes (Wrigley et al 2002;Moore and Diez Roux 2006;Chen and Florax 2010;Thomsen et al 2015;Chen et al 2016), whereas other studies find no statistical link between food access and obesity, body mass, or weight (Burdette and Whitaker 2004;Sturm and Datar 2005;Jeffery et al 2006;Ford and Dzewaltowski 2010;Slack et al 2014). A second class documents significant differences in the food environment, where low food access areas are found to have different retail outlet mixes, including higher densities of convenience stores or fast food restaurants and lower densities of supermarkets, and then identifies how these differences might create higher prices, less product selection, and fewer nutritious products (Alwitt and Donley 1997;Moore and Diez Roux 2006;Blanchard and Matthews 2007;Alviola et al 2013).…”
Section: Food Access and Policymentioning
confidence: 91%
“…One class investigates the relationship between the local food environment and health outcomes. While this research offers mixed results, many studies do find a link between low food access and obesity, diabetes, and other health-related outcomes (Wrigley et al 2002;Moore and Diez Roux 2006;Chen and Florax 2010;Thomsen et al 2015;Chen et al 2016), whereas other studies find no statistical link between food access and obesity, body mass, or weight (Burdette and Whitaker 2004;Sturm and Datar 2005;Jeffery et al 2006;Ford and Dzewaltowski 2010;Slack et al 2014). A second class documents significant differences in the food environment, where low food access areas are found to have different retail outlet mixes, including higher densities of convenience stores or fast food restaurants and lower densities of supermarkets, and then identifies how these differences might create higher prices, less product selection, and fewer nutritious products (Alwitt and Donley 1997;Moore and Diez Roux 2006;Blanchard and Matthews 2007;Alviola et al 2013).…”
Section: Food Access and Policymentioning
confidence: 91%
“…Prior research based on cross sectional study of these data has established high rates of obesity compared to national estimates and variance in obesity by race and sex (see the most recent annual report conducted by the Arkansas Center for Health Improvement) . Furthermore, these data have enabled the study of statewide programs and policies such as the federal Fresh Fruits and Vegetables Program (FFVP) and local food access programs …”
mentioning
confidence: 99%
“…Recent studies have found that (i) elderly residents living in food deserts who do not own a vehicle are more likely than those with a vehicle to report food insufficiency (Fitzpatrick, Greenhalgh-Stanley, and Ver Ploeg 2016); (ii) exposure to food deserts is correlated with higher body mass index scores among elementary schoolchildren (Thomsen et al 2016); and (iii) increased access to large supermarkets, grocery stores, and convenience stores in metropolitan deserts and health outcomes, there is limited evidence supporting the assumption that improved access will alter eating patterns . In fact, Cummins, Flint, and Matthews (2014) evaluate the impact of opening a new supermarket in a food desert and find that while the intervention increased residents' awareness of food accessibility, it did not lead to changes in dietary habits over the four years of the study.…”
mentioning
confidence: 99%